Time for a new (but not 'New') Fowler. Issue 2 (15th February 2016) - Straaijer, Robin
Abstract : Is English usage changing more rapidly than it was before? Judging by the decreasing time between editions of 'Fowlers' it would seem so: thirty-nine years between Fowler's Dictionary of Modern English Usage (1926, from here on MEU1 ) and Gower's second edition (1965, from here on MEU2 ), and thirty-one years between the latter and Burchfield's The New Fowler's Modern English Usage (1996, from here on NFMEU ). This led Manfred Görlach to write in his review of NFMEU that '[t]imes change, and we (and usage) change with them. A new edition of Fowler's classic book is thus in order every thirty to forty years' (Görlach, 1997).